The objectives of this research are identifying factors that influence the farmer’s decision to develop human resources and analyzing the role of human resources development to the income of farmer household. Theoretical framework based on the analysis of farmer household economic using descriptive analysis and econometric using single equation. The research location at province of Yogyakarta Province that are Bantul District represent coastal area and Kulon Progo District represents mountaino - Demitria Dewi; Harianto .; Sjafri Mangkuprawira; Nunung Kusnadi (Forum Pasca Sarjana, 2010)
The objectives of this research are identifying factors that influence the farmer’s decision to develop human resources and analyzing the role of human resources development to the income of farmer household. Theoretical framework based on the analysis of farmer household economic using descriptive analysis and econometric using single equation. The research location at province of Yogyakarta Province that are Bantul District represent coastal area and Kulon Progo District represents mountainous area. The result of economic analysis shows factors that influence the farmer’s decision to make activity in human resources investment are farmer’s motivation, farmer’s education, amount of family members, farmer’s savings, perceptions toward human resources development and relation with organization. Investment for human resources development at coastal area is higher than at mountainous area. The income of farmers at coastal area influenced by education investment and health investment, while the income of farmers at mountainous area influenced by farmers education and family member education. The implication of this research are the government facilitate better education and health services for farmers household, in order to access finance and market organization easier, optimizing all institution at rural area. Key words: model of farmers household economic, human resources development and income of farmer household